Análise de eficiência para o mercado de fundos de investimentos em ações no Brasil - Fonseca Junior, Esaú Alves da (2011)
Based on the literature and papers that investigate the hypothesis of efficiency of stock markets through the unit root tests in panel, the aim of this paper is to extend this methodology to the investment fund market in stocks, applying efficiency tests for this type of market for a non-random sample of 20 investment funds based on shares of the Brazilian market, using for this purpose, tests that correct feature panel data known as cross dependence, a fact which aims to give validity to the results. This work makes use of the Levi, Lin, Shun and In, Pesaran, Chin tests, accommodating interdependence between units crossaction of the panel. The main result to be achieved is to show the presence of a unit root in the dynamic characteristic of the indices in these investment funds in stocks, consistent, and with the efficiency hypothesis also checking if the results are consistent with national and international literature, revisiting the works that have employed panel tests that do not take into consideration the issue of cross-dependence.